Pengaruh Return On Equity, Return On Asset, dan Net Profit Margin Terhadap Harga Saham di Industri Manufaktur Sektor Consumer Goods Industry yang terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Marbun, Natasha P.; Yunior, Khomeiny; Fauzi, Fauzi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of the research is to analyze the relationship between Return On Equity (ROE), Return on Asset (ROA), and Net Profit Margin (NPM) with the price of shares of the consumer goods manufacturing industry listed on the Indonesian Stock Exchange (BEI) during the period 2017-2020. In order to determine the profitability of a company over a certain period of time, the ratio of profitability needs to be considered. The price of the stock is influenced by changes in demand and supply, which are affected by the rate of return on the company's profits. The observation population consists of 53 consumer product organizations recorded during the EIB period. A sample of 24 companies in the consumer product industry was selected using purposive sampling techniques. The research uses quantitative research strategies with data analysis involving traditional statistical methods, including normality, multicolinearity, heterocadastisity, and autocorrelation tests. The hypothesis was tested using double regression analysis. Research shows that the share price of consumer product companies in the EIB from 2017 to 2020 is partially influenced by ROE, ROA, and NPM, with each metric having a significant effect and corresponding value. The NPM is 0.673 > 0.05, the ROA is 0,000 < 0.05, and the ROE is 0.066 > 0.05. Companies in the consumer product sector listed in the EIB are significantly affected by ROE, ROA, and NPM from 2017 to 2020 (Sig. 0.000 < 0.05).